Department of Health customized procurement manual - Philippine. Department of Health. Procurement Service (Manila : DOH, 2010)
Vol. 1 guidelines on the establishment of procurement systems and organizations -- Vol. 2 manual of procedures for the procurement of goods -- Vol. 3 manual of procedures for the procurement of infrastructure projects -- Vol. 4 manual of procedures for the procurement of consulting service
Keywords: Government purchasing -- Philippines